THE DEBT-GROWTH RELATIONSHIP IN THE WESTERN BALKANS, DEVELOPING EUROPE, AND THE EUROZONE ECONOMIES: TESTING FOR THE EXISTENCE OF A TIPPING POINT (The South East European Journal of Economics and Business, 2025)
This paper examines the impact of public debt on economic growth in European regions, focusing on two objectives: first, to determine whether a threshold exists in the debt-growth relationship beyond which debt impedes growth, and second, to assess whether this threshold varies across regions. Using a threshold regression model, the analysis confirms such thresholds and identifies distinct levels: 22.2 percent for the Western Balkans, 37.4 percent for selected emerging European economies, and 82.6 percent for the Eurozone. These findings show that the debt-growth threshold depends on factors like economic structure and debt management capacity, suggesting a uniform debt management approach is ineffective. Instead, tailored strategies are needed to address regions’ unique economic contexts. By identifying specific thresholds, this research provides valuable insights for policymakers, guiding fiscal strategies that balance stability and growth while considering regional dynamics. The paper contributes to the discourse on debt sustainability and supports informed decision-making for resilience.